The effect of different community development activities as corporate social responsibility (CSR) programs to company profitability in the property industry of the Philippines for the period of 2019-2022 - Hamoy, Kristina Melisa E. (Animo Repository, 2023)
An individual’s perspective of a company or organization is impacted by corporate social responsibility (CSR), which can also have an impact on their overall financial performance. The study focuses on a specific CSR program called community development and the five (5) activities/programs that fall under it, namely, livelihood, education, medical, outreach, and housing. The study provides data that examines the costs incurred by businesses in the property industry of the Philippines in connection with the declared CSR activities under Community Development. According to the findings of the regression analysis used in this study, investment in housing community development activities has a considerable impact on businesses' financial success in terms of net profit margin. However, given that the majority of the studies produced insignificant results, it can be inferred that the CSR has no significant impact on a company's overall profitability. Additionally, other community development initiatives including outreach, education, and medical have no impact on the profitability of the companies in the property industry in the Philippines.